Ekspresja tworzenia czy akt zniszczenia? – problematyka graffti w świetle wybranych aspektów prawnokarnych - Dajnowicz-Piesiecka, Diana (Studia Prawnoustrojowe, 2019)
This article presents a phenomenon that everyone we pass every day, but not everyone sees it immediately. Going to work or school, shopping or walking next to each other, almost every day we pass the drawings and inscriptions which someone painted on the facades of buildings, or even on the means of communication. This direct contact with the graffti was an inspiration to discuss the phenomenon from the perspective of selected aspects of criminal law. The main objective, which was accompanied by the formation of the article, was to determine the boundary between legal and illegal graffti. Bearing in mind that graffti is a specifc form of artistic activities, the detailed analysis of the circumstances indicating that the graffti goes beyond the boundaries of art and begins to be the result of vandalism. Drawing or writing in public space also served to discuss the specifcs of halved acts. In addition, the article explains how to prevent and fghting against the phenomenon of graffti, which were undertaken on a national scale, as well as global. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">